Fractured Discourse: A Report from the Second International Conference on Cultural Policy Research - "Cultural Sites, Cultural Theory, Cultural Policy" - Jeannotte, M. Sharon (Université d'Ottawa | University of Ottawa, 2002)
The principal focus of many interventions was the “fracturing” of cultural policy discourse and research. In several cases, presenters stated quite bluntly that cultural policy had lost its way and had ceased to be a significant player in either culture or policy, at least at the national level.
Keywords: Cultural policy; Cultural research